2007
DOI: 10.1086/518125
|View full text |Cite
|
Sign up to set email alerts
|

The Look‐back Time Evolution of Far‐Ultraviolet Flux from the Brightest Cluster Elliptical Galaxies at z < 0.2

Abstract: We present the GALEX UV photometry of the elliptical galaxies in Abell clusters at moderate redshifts (z < 0.2) for the study of the look-back time evolution of the UV upturn phenomenon. The brightest elliptical galaxies (M r −22) in 12 remote clusters are compared with the nearby giant elliptical galaxies of comparable optical luminosity in the Fornax and Virgo clusters. The sample galaxies presented here appear to be quiescent without signs of massive star formation or strong nuclear activity, and show smoot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 72 publications
0
26
2
Order By: Relevance
“…The evolution of the strength of the UV upturn with redshift (z) has been tackled by numerous articles (e.g. Brown et al 1998Brown et al , 2000Brown 2004;Rich et al 2005;Ree et al 2007). While Rich et al (2005) have analysed a potential trend in the (FUV-r) colour in z bins, no correlation was found.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the strength of the UV upturn with redshift (z) has been tackled by numerous articles (e.g. Brown et al 1998Brown et al , 2000Brown 2004;Rich et al 2005;Ree et al 2007). While Rich et al (2005) have analysed a potential trend in the (FUV-r) colour in z bins, no correlation was found.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery (Code & Welch 1979), it has been known for several decades that some giant elliptical galaxies exhibit a strong unexpected bump in the UV part of the spectrum (see O'Connell 1999, for a review). Recent Galaxy Evolution Explorer (GALEX) observations indicate that the UV flux excess is most significant in BCGs (Ree et al 2007). The observed UV excess, also known as the UV upturn, is spatially smooth and extended (e.g., Lee et al 2005a;Ree et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent Galaxy Evolution Explorer (GALEX) observations indicate that the UV flux excess is most significant in BCGs (Ree et al 2007). The observed UV excess, also known as the UV upturn, is spatially smooth and extended (e.g., Lee et al 2005a;Ree et al 2007). The spatial distribution and the spectral shape of the UV upturn phenomena cannot be explained by recent star formation (Brown et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Peng and Nagai (2009) have explained the typically more strong UV-upturns in the spectra of BCGs by the helium sedimentation in the intracluster medium of galaxy clusters: helium-rich stars evolve faster and burn more hydrogen so a very large He abundance (Y > 0.40) can greatly boost the UV upturn strength (Dorman et al 1995). Atlee et al (2009) who have studied luminous early-type galaxies in a variety of environments in the redshift range of 0.05-0.65, after stacking hundreds of GALEX spectra in the redshift bins, have found that while at z = 0.2 their data are in agreement with the data of Ree et al (2007) and so favour the 'metal-poor, horizontal branch' hypothesis, at z > 0.3 they reverse their trend with the redshift and begin to contradict all the models of UV-upturn producing by single old stars.…”
Section: Elliptical Galaxies: Theorymentioning
confidence: 53%
“…The successful attempt to follow this way has been recently undertaken with the UV cosmic telescope GALEX. In the work by Ree et al (2007) the brightest elliptical galaxies in 12 remote clusters are compared with the nearby giant elliptical galaxies of the same optical luminosity belonging to the Fornax and Virgo clusters. The observed fading in FUV flux with redshift agrees well with the prediction from the population synthesis models where the dominant FUV sources are hot horizontal-branch stars so supporting the 'metal-poor' hypothesis.…”
Section: Elliptical Galaxies: Theorymentioning
confidence: 99%